2016
DOI: 10.5194/amt-9-3031-2016
|View full text |Cite
|
Sign up to set email alerts
|

The role of cloud contamination, aerosol layer height and aerosol model in the assessment of the OMI near-UV retrievals over the ocean

Abstract: Retrievals of aerosol optical depth (AOD) at 388 nm over the ocean from the Ozone Monitoring Instrument (OMI) two-channel near-UV algorithm (OMAERUV) have been compared with independent AOD measurements. The analysis was carried out over the open ocean (OMI and MODerate-resolution Imaging Spectrometer (MODIS) AOD comparisons) and over coastal and island sites (OMI and AERONET, the AErosol RObotic NETwork). Additionally, a research version of the retrieval algorithm (using MODIS and CALIOP (Cloud-Aerosol Lidar … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 67 publications
(89 reference statements)
0
20
0
Order By: Relevance
“…Schoeberl et al (2007) further used a wind trajectory mapping technique of MLS ozone profiles and used potential vorticity mapping to obtain better signal-to-noise ratio and horizontal coverage for the OMI/MLS tropospheric column ozone. Wargan et al (2015) discusses an OMI/MLS ozone profile product derived using data assimilation; it is noted that current MERRA-2 (Gelaro et al, 2017;Wargan et al, 2017) analyses include ozone profiles determined similarly via data assimilation of Aura MLS and OMI ozone. A comparison of several OMI/MLS tropospheric column ozone products (data assimilation, trajectory mapping, and profile retrieval methods) is described by Ziemke et al (2014).…”
Section: Multi-instrument Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schoeberl et al (2007) further used a wind trajectory mapping technique of MLS ozone profiles and used potential vorticity mapping to obtain better signal-to-noise ratio and horizontal coverage for the OMI/MLS tropospheric column ozone. Wargan et al (2015) discusses an OMI/MLS ozone profile product derived using data assimilation; it is noted that current MERRA-2 (Gelaro et al, 2017;Wargan et al, 2017) analyses include ozone profiles determined similarly via data assimilation of Aura MLS and OMI ozone. A comparison of several OMI/MLS tropospheric column ozone products (data assimilation, trajectory mapping, and profile retrieval methods) is described by Ziemke et al (2014).…”
Section: Multi-instrument Retrievalsmentioning
confidence: 99%
“…For example, in the OMAERUV aerosol product, data from the CALIOP have been used to constrain the aerosol layer heights, and carbon monoxide (CO) data from AIRS have been used to help distinguish different types of absorbing aerosol, i.e., smoke from dust (Torres et al, 2013). MODIS data (OMMYDCLD) have been used to evaluate the effect of subpixel cloud contamination (Gassó and Torres, 2016). AOTs from MODIS have also been combined with OMI measurements to estimate aerosol layer height (Satheesh et al, 2009;Chimot et al, 2017).…”
Section: Aerosol Productsmentioning
confidence: 99%
“…Desert dust aerosols are known to be irregularly shaped large particles whose phase function may deviate significantly from that of a spherical model at scattering angles larger than about 80° for non-10 absorbing particles. The role of particle shape assumption in the retrieval of desert dust properties was recently identified as an important source of uncertainty in the OMAERUV algorithm [Gassó and Torres, 2016]. An analysis of the uncertainty in retrieved AOD and SSA associated with the spherical shape assumption of desert dust particles is presented next.…”
Section: Row Anomalymentioning
confidence: 99%
“…OMAERUV quantitative aerosol products have been evaluated by comparison to independent ground-based observations 10 [Torres et al, 2007;Ahn et al, 2014;Jethva et al, 2014, Zhang et al, 2016, airborne measurements [Livingston et al, 2009] as well as to other satellite measurements [Ahn et al, 2008;Gassó and Torres, 2016].…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al [35] simulated the uncertainties from the particle shape and refractive index with the Ping Yang database, and pointed out that the particle shape effect is found to be related to the dust optical depth and the surface albedo can be an important uncertainty source in radiative transfer simulation. Even though near-UV measurement is insensitive to aerosol phase function effects, as discussed by Torres et al [10], the research done by Gasso et al [38] showed that the dust LUT applied by the T-matrix code resulted in an increasing retrieval of AOD. However, a non-spherical model did not affect to SSA retrieved results, as noted by Kroktov et al [39] and Dubovik et al [26].…”
Section: Conflicts Of Interestmentioning
confidence: 99%